Metabolic adjustments in Satanoperca aff. jurupari (Perciformes: Cichlidae) - Chippari-Gomes,Adriana R. (2003)
In this paper, we describe the enzyme levels and isozyme distribution in skeletal and heart muscle of Satanoperca aff. jurupari, (Cichlidae, subgroup Geophaginae). LDH and CS were measured in skeletal and heart muscle. Starch gel electrophoresis was used to determine the isozyme/allozyme patterns in different tissues; LDH, MDHs, PGM, PGI, ADH, G-6-PDH and SOD were screened for the numbers of loci, presence of alleles, and tissue specificity. The LDH/CS ratio in heart and skeletal muscle were 173.36 and 6.1, respectively, indicating anaerobic metabolism in the former and aerobic metabolism in the latter muscle. No inhibition by pyruvate (based on the ratios of LDH activity with 1 mM and 10 mM pyruvate) was detected in heart and skeletal muscle, indicating the presence of physiological plasticity in heart muscle. The heart can cope with anaerobic metabolism for short periods of hypoxia such as occurs in nature. Isozyme patterns for most of the enzymes analyzed were similar to the general patterns for advanced teleosts. S. aff. jurupari had no reduced LDH-B* expression in heart muscle, but the, MDHs-B* locus was duplicated, as reported for most Amazon cichlids species. Only three out of the 13 loci analyzed (PGM, PGI and SOD) were variable. These results are consistent with the metabolic profile and life style of the most cichlids. A low genetic variability may be a counterpart for plasticity, and may be guaranteed by the regulation of invariable structural genes.